Hubungan Gejala Menopause dan Insomnia pada Pra-lansia: Penelitian - Ekowati, Ana Lucia; Verena, Geneta; Tjhay, Francisca; Joprang, Freggy Spicano (Cermin Dunia Kedokteran, 2026)
Introduction: Menopause causes somatic, psychological, and urogenital symptoms as risk factors for insomnia. This study aims to determine the relationship between menopause symptoms and insomnia in the pre-elderly. Methods: Descriptive analytical study using a cross-sectional method. The variables in this study were menopause symptoms and the severity of insomnia as measured by the MRS and ISI questionnaire. The sample consisted of 107 pre-elderly menopausal women at a church in South Tangerang, using the convenience sampling method. Data analysis included univariate analysis (descriptive statistics) to examine sample characteristics and bivariate analysis with the Kruskal-Wallis test to examine the relationship between menopausal symptoms and the severity of insomnia. Results: A significant relationship between menopause symptoms and the severity of insomnia (p < 0.05). Based on each insomnia severity, the highest mean rank of respondents who experienced moderate clinical insomnia had somatic symptoms (90.44), the highest mean rank of respondents who experienced subthreshold insomnia had psychological symptoms (75.59), and the highest mean rank of respondents who did not experience insomnia had urogenital symptoms (42.91). Conclusion: Menopause symptoms are significantly related to the severity of insomnia in pre-elderly individuals.